Art across time - Adams, Laurie (McGraw-Hill, 2007)
Art Across Time is a comprehensive art history text that engages the mind of the reader by considering the place of images within the cultures that create them, even as it engages the eye with fabulous color reproductions that are two- and three-times the size of comparable images in other textbooks.